The relationship between preseason range of motion and muscle strain injury in elite soccer players - Bradley, P. S.; Portas, M. D. (The Journal of Strength and Conditioning Research, 2007)
The purpose of the study was to determine the influence of preseason lower-extremity range of motion (ROM) on the risk of muscle strain injury during a competitive season for elite soccer players. Thirty-six elite male soccer players (age, 25.6 = 4.7 years) had maximum static ROM for 6 movements of the lower extremity measured prior to the 2003-2004 English Premier League season. Player age, body size, dominant limb, and playing position were documented also. All lower-extremity muscle strain injuries were recorded prospectively during the competitive season, as was the total amount of time spent in training and games for each player. Soccer players sustaining a muscle strain injury in the hip flexors or knee flexors had lower pre- season ROM (p <= 0.05) in these muscle groups compared with uninjured players. Similar trends were observed for the remaining muscle groups, but all failed to reach statistical significance (p >= 0.05). Most significantly, soccer players with lower preseason ROM in the hip flexors and knee flexors had a statistically higher risk for a muscle strain injury to these muscle groups during a competitive season. Age, body size, limb dominance, and playing position were not significant intrinsic risk factors for the development of muscle strain injuries. Screening of flexibility for soccer players should be conducted during preseason, and flexibility training should be prescribed to players with reduced ROM to lower the risk of developing a muscle strain injury.